1996
DOI: 10.1016/s0735-1097(96)00397-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Findings and Outcome in Diabetic Patients Treated With Thrombolytic Therapy for Acute Myocardial Infarction: The GUSTO-I Experience

Abstract: Early (90-min) infarct-related artery patency as well as regional and global ventricular function do not differ between patients with and without diabetes after thrombolytic therapy, except for reduced compensatory hyperkinesia in the noninfarct zone among patients with diabetes. Diabetes remained an independent determinant of 30-day mortality after correction for clinical and angiographic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
165
3
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(183 citation statements)
references
References 42 publications
10
165
3
4
Order By: Relevance
“…Although current treatment of AMI with fibrinolytic agents and aspirin has led to a marked improvement in the prognosis for AMI [18,19], diabetic patients remain a subgroup at high risk of mortality, both in hospital and after discharge, and diabetes still doubles the case fatality rate [5,7,20]. The results of the present study confirm this, as diabetes status in itself accounted for an increase in the risk of 3-year global mortality by a factor of 1.9.…”
Section: Discussionsupporting
confidence: 79%
“…Although current treatment of AMI with fibrinolytic agents and aspirin has led to a marked improvement in the prognosis for AMI [18,19], diabetic patients remain a subgroup at high risk of mortality, both in hospital and after discharge, and diabetes still doubles the case fatality rate [5,7,20]. The results of the present study confirm this, as diabetes status in itself accounted for an increase in the risk of 3-year global mortality by a factor of 1.9.…”
Section: Discussionsupporting
confidence: 79%
“…This is of major public health importance since patients with type 2 diabetes are at increased risk of developing and dying from cardiovascular disease, which accounts for up to 70% of deaths in this population [2]. The epidemiology and characteristics of coronary artery disease in type 2 diabetes are well described in the literature [3][4][5][6][7]. The focus in reducing cardiovascular deaths in diabetes tends almost exclusively to be on reducing fresh coronary events.…”
Section: Introductionmentioning
confidence: 99%
“…This was probably due to lower efficacy of fibrinolytic agents in diabetic patients who are characterized by increased procoagulation activity and impaired endogenous fibrinolysis. 24,25 In accordance with the new guidelines for treatment of patients with STEMI, primary PTCA is the best strategy of treatment in diabetic patients. The Global Utilization of Streptokinase and tPA for Occluded Arteries study showed that the reinfarction rate at 30 days was lower in diabetic individuals undergoing primary PTCA as compared with fibrinolysis.…”
Section: Resultsmentioning
confidence: 99%